Nihilism and absolute tragedy in the post-secular age: Contributions from liberation theology - Frontán, Federico (2025)
The advances of neoconservative sectors in the West show that we are in a postsecular era. The utopian right achieved its political rise thanks to its ability to mobilize some of the oldest myths. Therefore, it is of utmost importance to consider the links between tragedy and the philosophical systems that give it meaning. By relating nihilism, tragedy and utopia in the Western tradition, this article proposes to value the «potential for reason» that the theory of tragedy has in the West. We are interested in the perspective of Latin American liberation theology.